Uso de dejetos bovinos e suínos como fertilizantes: avaliação dos efeitos ecotoxicológicos em minhocas Eisenia andrei - Weiss, Daiane (2024)
The global production of pigs and cattle, although playing an important role in the economy, can generate significant environmental impacts, such as those associated with waste generated in intensive animal production. This study aims to investigate the ecotoxicological impact on earthworms exposed to soils historically fertilized with pig and cattle waste, as well as the longterm effects of soil applications (argisol). The methodology included the analysis of soil physicochemical characteristics and the evaluation of biomarkers in animals, such as: antioxidant capacity against peroxyl radicals (ACAP), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), hydrogen peroxide (H2O2), reactive oxygen species (ROS), protein carbonylation, thiobarbituric acid reactive substances (TBARS), acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). Earthworms were exposed to the following treatments: Control (CT), Liquid Cattle Manure (DLB), Liquid Swine Manure (DLS), and Swine Deep Bedding (CSS), for 28 days, with biomarker evaluation at 14 and 28 days, with tests conducted in quadruplicate. Statistical analysis included Kruskal-Wallis and ANOVA tests with a significance level of p < 0.05. The results revealed an interaction between manure treatments, soil, and earthworms. The increase in levels of K, Ca, Mg, Cu, Zn, and Mn in DLB suggests a more fertile environment but also more prone to oxidative stress. Antioxidant enzymes (SOD and CAT) show increased activity over time, indicating an adaptive response to TBARS oxidative damage and protein carbonylation, indicating oxidative stress. In this scenario, the increase in AChE and inhibition of BChE indicate possible neurotoxic effects. In DLS, levels of P, K, Cu, and Zn show increased activity of antioxidant enzymes (ACAP, SOD, CAT, and GST), cholinergic activity (AChE), inhibition of GPx and BChE, increased H2O2, and maintenance of other oxidative damage markers. The presence of Ni at higher levels may have contributed to the observed toxicity and oxidative stress. The increase in BChE activity may be an adaptive response to counterbalance the elevated AChE activity and try to restore neurological balance. CSS has the highest levels of CoT, NT, CTC, Cu, Zn, and Mn. These factors lead to a significant increase in antioxidant enzyme activity and oxidative damage markers, suggesting a high level of oxidative stress. The same effect observed for cholinesterases in DLS was observed in this treatment. These results indicate changes in the functioning of enzymes related to neurological function in organisms. The increase in antioxidant enzyme activity over time in waste treatments shows an adaptation to oxidative damage caused by the glutathione pathway, mainly by GST regenerating GSH, with possible neurotoxic effects and oxidative stress observed in the different treatments. Therefore, the application of waste over time in the soil can negatively impact earthworms, impairing their ecological functions and affecting the health and biodiversity of the ecosystem as a whole.